Observation of Higgs boson decay to bottom quarks - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (American Physical Society, 2018)
The observation of the standard model (SM) Higgs boson decay to a pair of bottom quarks is presented. The main contribution to this result is from processes in which Higgs bosons are produced in association with a W or Z boson (VH), and are searched for in final states including 0, 1, or 2 charged leptons and two identified bottom quark jets. The results from the measurement of these processes in a data sample recorded by the CMS experiment in 2017, comprising 41.3 fb−1 of proton-proton collisions at ffiffi s p ¼ 13 TeV, are described. When combined with previous VH measurements using data collected at ffiffi s p ¼ 7, 8, and 13 TeV, an excess of events is observed at mH ¼ 125 GeV with a significance of 4.8 standard deviations, where the expectation for the SM Higgs boson is 4.9. The corresponding measured signal strength is 1.01 0.22. The combination of this result with searches by the CMS experiment for H → bb¯ in other production processes yields an observed (expected) significance of 5.6 (5.5) standard deviations and a signal strength of 1.04 0.20.